Carbon Monoxide: A Pleiotropic Redox Regulator of Life and Death - Andrey Y. Abramov; Isabella Myers; Plamena R. Angelova (MDPI AG, 2024)
Despite recent technological progress, carbon monoxide poisoning is still one of the leading causes of domestic and industrial morbidity and mortality. The brain is particularly vulnerable to CO toxicity, and thus the majority of survivors develop delayed movement and cognitive complications. CO binds to haemoglobin in erythrocytes, preventing oxygen delivery to tissues, and additionally inhibits mitochondrial respiration. This renders the effect of CO to be closely related to hypoxia reperfusion injury. Oxygen deprivation, as well as CO poisoning and re-oxygenation, are shown to be able to activate the production of reactive oxygen species and to induce oxidative stress. Here, we review the role of reactive oxygen species production and oxidative stress in the mechanism of neuronal cell death induced by carbon monoxide and re-oxygenation. We discuss possible protective mechanisms used by brain cells with a specific focus on the inhibition of CO-induced ROS production and oxidative stress.